2021
DOI: 10.21608/ejchem.2021.86363.4178
|View full text |Cite
|
Sign up to set email alerts
|

Different Cleaning Techniques for Removal of Iron stain from Archaeological Bone Artifacts: A Review

Abstract: Archaeological bone artifacts are found in different locations in Egypt, and they represent multiple values that should be preserved from different deterioration factors. Iron contamination is considered one of the most aspects of deterioration for bones extracted from excavation areas. This study aims to make an integrated study for the first time on the formation of iron rust stain on archaeological bones, explain the aspects and mechanism of its deterioration, explain traditional and advanced techniques of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Usually, hydrogen gas has been widely employed in plasma treatment based on the fact that most of the corrosion products are metal oxides or chlorides [21,22]. During this process, the hydrogen species will react with oxygen and chlorine, resulting in the formation of OH radicals and HCl molecules that can be consequently removed from the reaction system [23,24]. Compared to the traditional methods, the modern plasma chemical treatment is a dry method, which prevents further corrosion caused by water during the treatment [25].…”
Section: Introduction and Research Aimmentioning
confidence: 99%
“…Usually, hydrogen gas has been widely employed in plasma treatment based on the fact that most of the corrosion products are metal oxides or chlorides [21,22]. During this process, the hydrogen species will react with oxygen and chlorine, resulting in the formation of OH radicals and HCl molecules that can be consequently removed from the reaction system [23,24]. Compared to the traditional methods, the modern plasma chemical treatment is a dry method, which prevents further corrosion caused by water during the treatment [25].…”
Section: Introduction and Research Aimmentioning
confidence: 99%
“…The role of conservation processes is to protect the objects from adverse chemical action, increase their chemical stability, improve the appearance of the objects, give future resistance against unappropriated conditions, improve the mechanical properties, and reveal the aesthetic values [25][26][27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…plasma, a non-contact approach, when mixed with the aqueous extract, cleaned the surface of historical images without leaving stains or causing damage. Abdel-Maksouda, et al [33] described the role of plasma cleaning in removing iron stains from archaeological bone artefacts and demonstrated that plasma-based technology is one of the most promising techniques for the preservation of cultural heritage. Abdel-Maksoud, et al [34] explained that the pulsed coaxial plasma pistol is an excellent and quick technique to remove invisible oil coatings, dust deposits, corrosion products, and other contaminants from bone.…”
Section: Introductionmentioning
confidence: 99%